Long Term Results of Pancreatectomy With and Without Venous Resection: A Comparison of Safety and Complications of Spiral Graft, End-to-End and Tangential/Patch Reconstruction Techniques. (August 2022) - Vuorela, Tiina; Vikatmaa, Pirkka; Kokkola, Arto; Mustonen, Harri; Salmiheimo, Aino; Eurola, Annika; Aho, Pekka; Haglund, Caj; Kantonen, Ilkka; Seppänen, Hanna
Abstract : Objective: Roughly 10% – 20% of pancreatic cancer patients are candidates for curative intent surgical treatment. In the 2000s, many studies showed similar survival rates comparing pancreatic surgery with or without vein resection and reconstruction. The aim was to identify the best method of venous reconstruction. Methods: This was a retrospective cohort study. A total of 1 375 patients undergoing pancreatectomy between 2005 and 2018 were identified. Patients undergoing a combined pancreatic resection and venous reconstruction were included retrospectively. When tumour infiltration to the portal/superior mesenteric vein was detected, excision and reconstruction with tangential suturing/patch, end to end anastomosis, or a spiral graft from the great saphenous vein was performed. Next, 90 day and long term survival and outcomes across reconstruction techniques were analysed. Results: Overall, 198 patients had venous involvement visible in pre-operative scans or detected during surgery, broken down as follows: 171 (86%) pancreaticoduodenectomy, 12 (6%) total pancreatectomy, and 15 (8%) distal pancreatectomy. In total, 69 (35%) spiral graft reconstructions, 77 (39%) end to end anastomoses, and 52 (26%) tangential/patch reconstructions were performed. Tumour histology revealed pancreatic adenocarcinomas in 162 (82%) patients, intraductal mucinous pancreatic neoplasia in 14 (7%), cholangiocarcinoma in five (3%), neuro-endocrine neoplasia in nine (5%), and eight other diagnoses. Overall, 183 (92%) were malignant and 15 (8%) benign. Two patients died within 90 days, one in hospital and one on post-operative day 38 due to thrombosis of the superior mesenteric vein and intestinal necrosis, a Clavien–Dindo grade 5 complication. In addition, 50 (23%) patients had Clavien–Dindo grade 3 – 4 complications. No differences in complications comparing vein reconstruction techniques or in the long term survival of pancreatectomy patients with or without venous reconstruction were detected. Conclusion: The spiral graft technique, used when more advanced venous infiltration occurs, does not increase complications, with outcomes mirroring those accompanying shorter venous resections.